RETRACTED: Microlearning helps Alzheimer’s Disease Patients - Hu, Jiayao (EAI Endorsed Transactions on e-Learning, 2023)
RETRACTED: The article has been retracted due to misconduct during the peer review process. The retraction notice can be found here: https://doi.org/10.4108/eetel.12285
Keywords: Microlearning; Alzheimer’s disease; Machine learning; Just-in-Time Learning; Learners; Bite-Sized Learning Units; Caregivers; Healthcare